Subspace Almost Periodic C-Distribution Semigroups and C-Distribution Cosine Functions - M. Kostic, S. Pilipovic, D. Velinov (Faculty of Sciences and Mathematics, University of Nis, Serbia, 2017)
The main aim of this paper is to introduce and analyze the notations of subspace almost periodicity and subspace weak almost periodicity for C-distribution semigroups and C-distribution cosine functions in Banach spaces. We continue our previous research study of almost periodicity of abstract Volterra integro-differential equations, focusing our attention on the abstract ill-posed Cauchy problems of first order.
Keywords: C-distribution semigroups, C-distribution cosine functions, Integrated C-semigroups, Integrated C-cosine functions, Subspace almost periodicity